MODEL FOTOKIMIA UNTUK SIMULASI OZON PERMUKAAN - puslit, Rukmi Hidayati; Budiyono, Afif; Nugraha, Sarwito Agung; Mulyono, Mulyono (Jurnal Teknologi Lingkungan Universitas Trisakti, 2008)
Photochemical model for ozone surface simulation. Mathematical model is needed to study the highly reactive trace species as their data are sparse and difficult to measure such as as nitric oxide (NO), nitrogen dioxide (NO2), ozone (O3), and carbon oxide (CO). The main principles applied in the integration of the chemical part are based on a mass balance of species by considering that both chemical and physics processes are solvable with Euler number technique and the assumption of